2017
DOI: 10.18632/oncotarget.19167
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation and deacetylation in cancer stem-like cells

Abstract: Cancer stem-like cell (CSC) model has been established to investigate the underlying mechanisms of tumor initiation and progression. The imbalance between acetylation and deacetylation of histone or non-histone proteins, one of the important epigenetic modification processes, is closely associated with a wide variety of diseases including cancer. Acetylation and deacetylation are involved in various stemness-related signal pathways and drive the regulation of self-renewal and differentiation in normal developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 106 publications
0
59
0
5
Order By: Relevance
“…HDACs work in equilibrium with histone acetyl transferases to control the acetylation level of proteins and influence diverse biological processes such as gene expression (Sterner & Berger, 2000), protein trafficking (Li & Yang, 2015), and the innate immune response (Zhou, He, Wang, & Ge, 2017). Consequently, the imbalance in protein acetylation due to aberrant function of HDACs or histone acetyl transferases contributes to multiple human diseases such as cancer (Liu, Li, Wu, & Cho, 2017), neurodegeneration (Cook, Stankowski, Carlomagno, Stetler, & Petrucelli, 2014), and infection (Jeng, Ali, & Ott, 2015;Song & Walley, 2016). So far, 18 HDACs have been identified in human HDAC family and classified into four classes (Seto & Yoshida, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…HDACs work in equilibrium with histone acetyl transferases to control the acetylation level of proteins and influence diverse biological processes such as gene expression (Sterner & Berger, 2000), protein trafficking (Li & Yang, 2015), and the innate immune response (Zhou, He, Wang, & Ge, 2017). Consequently, the imbalance in protein acetylation due to aberrant function of HDACs or histone acetyl transferases contributes to multiple human diseases such as cancer (Liu, Li, Wu, & Cho, 2017), neurodegeneration (Cook, Stankowski, Carlomagno, Stetler, & Petrucelli, 2014), and infection (Jeng, Ali, & Ott, 2015;Song & Walley, 2016). So far, 18 HDACs have been identified in human HDAC family and classified into four classes (Seto & Yoshida, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation in epigenetic programming has been linked to tumorigenesis, possibly through induction of a stemness phenotype (Hadjimichael et al, 2015). Histone acetylation status is related to cancer stemness regulation, and HDAC inhibition constitutes an important therapeutic strategy to induce differentiation in CSCs (Liu et al, 2017). Abnormal epigenetic regulation related to histone modifications have been recently reported in SHH MB .…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation can regulate the functions of nonhistone proteins by altering protein stability, subcellular localization, and protein–nucleic acid/protein–protein interactions (Narita, Weinert, & Choudhary, ). Recent studies have shown that the acetylation of many nonhistone proteins is associated with tumorigenesis, cancer cell proliferation, and immune function, which makes the regulation of protein acetylation a potential approach for the treatment of cancer (de Almeida Nagata et al, ; Dou, Zheng, Liu, & Tu, ; Liu, Li, Wu, & Cho, ). At present, acetylation has been shown to be involved in many important biological processes, including cell apoptosis (Cohen et al, ; S. S. Choi, Rhee, & Park, ), subcellular localization (Fujita, Fujiwara, Zenitani, & Yamashita, ; Ishfaq et al, ; Ito et al, ), DNA replication and repair (Al Emam, Arbon, Jeeves, & Kysela, ; Ghosh, Bohr, & Karmakar, ), DNA and protein interactions (Ugrinova, Pashev, & Pasheva, ), DNA transcription (Asano, Czuwara, & Trojanowska, ), protein stability (J. R. Choi, Lee, Shin, Choi, & Kang, ; J. Y. Choi, Ko, & Jo, ; Ge, Jin, Zhang, Yan, & Zhai, ; Wei et al, ), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylation can regulate the functions of nonhistone proteins by altering protein stability, subcellular localization, and protein-nucleic acid/ protein-protein interactions (Narita, Weinert, & Choudhary, 2019). Recent studies have shown that the acetylation of many nonhistone proteins is associated with tumorigenesis, cancer cell proliferation, and immune function, which makes the regulation of protein acetylation a potential approach for the treatment of cancer (de Almeida Nagata et al, 2019;Dou, Zheng, Liu, & Tu, 2017;Liu, Li, Wu, & Cho, 2017). At present, acetylation has been shown to be involved in many important biological processes, including cell apoptosis (Cohen et al, 2004;S.…”
Section: Introductionmentioning
confidence: 99%